Design of a novel state-feedback robust $$H_2/H_{∞ }$$ sliding-mode controller for a hydraulic turbine governing system - Fang Dao; Yidong Zou; Jing Qian; Yun Zeng (Scientific Reports)
Abstract This paper presents a novel state-feedback robust sliding-mode controller (SFRSMC) based on a mixed $$H_2/H_{∞ }$$ H 2 / H ∞ approach to enhance the control performance of hydraulic turbine governing systems (HTGS) with complex conduit systems under external load disturbances and control signal uncertainties. A state-space model incorporating the dynamic responses of the HTGS is developed. The SFRSMC is designed using the sliding-mode equivalent control principle, with a disturbance observer to estimate and mitigate unknown disturbances. To balance robustness and optimality, mixed $$H_2/H_{∞ }$$ H 2 / H ∞ linear matrix inequalities (LMIs) are utilized to determine the critical performance sliding matrix via an auxiliary feedback control method. The effectiveness of the proposed control scheme is validated through time-domain simulations under various operating scenarios, including different parameter variations of the HTGS.